2022
DOI: 10.3390/encyclopedia2010012
|View full text |Cite
|
Sign up to set email alerts
|

The Apicomplexan Parasite Toxoplasma gondii

Abstract: Toxoplasma gondii is a ubiquitous zoonotic parasite with an obligatory intracellular lifestyle. It relies on a specialized set of cytoskeletal and secretory organelles for host cell invasion. When infecting its felid definitive host, T. gondii undergoes sexual reproduction in the intestinal epithelium, producing oocysts that are excreted with the feces and sporulate in the environment. In other hosts and/or tissues, T. gondii multiplies by asexual reproduction. Rapidly dividing tachyzoites expand through multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 200 publications
(334 reference statements)
1
14
0
Order By: Relevance
“…In the different age groups of cows showed that the prevalence of T. gondii DNA considerably increases with the age of the cow. The present research was coherent with the reported prevalence in cows from different countries such as 20% from Mohmand agency, Pakistan (Shah et al, 2013), 13.3% by ELISA from Sudan (Elfahal et al, 2013), 15.91% from Iran (Delgado et al, 2022), and all these support the present study. While the reported prevalence of T. gondii in cattle from Serbia the estimated prevalence of T. gondii was observed 76.3% in cattle (Klun et al, 2006), and from Brazil, 71% prevalence of T. gondii was reported in cattle (Santos et al, 2009) which was extremely higher than the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In the different age groups of cows showed that the prevalence of T. gondii DNA considerably increases with the age of the cow. The present research was coherent with the reported prevalence in cows from different countries such as 20% from Mohmand agency, Pakistan (Shah et al, 2013), 13.3% by ELISA from Sudan (Elfahal et al, 2013), 15.91% from Iran (Delgado et al, 2022), and all these support the present study. While the reported prevalence of T. gondii in cattle from Serbia the estimated prevalence of T. gondii was observed 76.3% in cattle (Klun et al, 2006), and from Brazil, 71% prevalence of T. gondii was reported in cattle (Santos et al, 2009) which was extremely higher than the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Experimental access to these stages is paramount to study the pathogenic mechanisms and to develop urgently needed therapies and vaccines. The most widespread member of the Apicomplexa is Toxoplasma gondii , causative agent of toxoplasmosis, which has a broad host range and can infect any warm-blooded animal and humans (for review see 1 , 2 ). An estimated 25% of the world’s population is infected with the parasite, with large local variations 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Parasites then differentiate into bradyzoites within tissue cysts that are found primarily in the eye, brain and muscle tissue ( Figure 1A ). In addition to this asexual replication, sexual recombination can take place in felines, the definitive hosts ( Figure 1C ) 1 . The sporozoite-containing oocysts formed during this process are shed into the environment with the feces and can withstand harsh environmental stresses such as ultraviolet irradiation, salinity, high and low temperatures, and desiccation, allowing them to remain infectious for months and even years ( Figure 1D ) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, they contribute to a spectrum of diseases with significant mortality rates, impacting billions of people worldwide. Malaria, cryptosporidiosis, and toxoplasmosis stand out as the primary diseases caused by parasites in this phylum 1 . These parasites effectively manipulate the infected cells to create the necessary niche for establishing the infection [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%